KEGIATAN VOICE OVER BERITA SEBAGAI BENTUK PRAKTIK BROADCASTING MAHASISWA DI SRIWIJAYA TV - Elma Tiana; Isnawijayani Isnawijayani; Desy Misnawati (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The development of broadcasting technology has significantly changed the landscape of television journalism. This study aims to describe the implementation of news voice-over activities as a form of practical broadcasting experience for students at Sriwijaya TV, explain the news production process involving voice-over, identify the challenges encountered, and analyze the benefits in enhancing students' professional competencies. The method used in this research is descriptive-qualitative based on field observations, involvement in production activities, and documentation during an internship program from March to June 2026. The results indicate that news voice-over plays a vital role in the post-production stage to clarify visual content and maintain news narrative flow. Students were actively involved in 35 broadcasting and voice-over packages for the 'Kabar Sriwijaya Malam' program, covering various public issues in Palembang. The main challenges included technical constraints in studio camera operations and field journalism difficulties, such as finding reluctant sources at local markets. These challenges were successfully overcome through consistent vocal practice, pre-interview adjustments, and intensive technical guidance from network mentors. This practical experience significantly improved students' technical skills in articulation, intonation, breath control, and enhanced their readiness for professional careers in the broadcast media industry.